2015
DOI: 10.1121/1.4920677
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in the perception of Mandarin tones: Evidence from mismatch negativity

Abstract: The mismatch negativity (MMN) component of the electroencephalogram reflects phonological asymmetries: specifically, greater MMN is elicited by infrequent (deviant) tokens when the features of the frequent (standard) token are phonologically underspecified than when those features are phonologically fully specified. Such asymmetries have not been studied in non-Indo-European languages or in suprasegmental contrasts, which might not be represented in the same way as segments. Therefore, the present study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Syllables in the 3rd position (XXY deviant) differ in their consonant voicing and place of articulation, and in their vowel height (Mioni, 1993;Kramer, 2009;Paoli, 2016). While it should be noted that whether all these phonological features have a neural representation is on itself an open debate (Hestvik and Durvasula, 2016;Politzer-Ahles et al, 2016;Schluter et al, 2016Schluter et al, , 2017, in the case of our stimuli set, the number of phonological features that change for each deviant condition is the same.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Syllables in the 3rd position (XXY deviant) differ in their consonant voicing and place of articulation, and in their vowel height (Mioni, 1993;Kramer, 2009;Paoli, 2016). While it should be noted that whether all these phonological features have a neural representation is on itself an open debate (Hestvik and Durvasula, 2016;Politzer-Ahles et al, 2016;Schluter et al, 2016Schluter et al, , 2017, in the case of our stimuli set, the number of phonological features that change for each deviant condition is the same.…”
Section: Discussionmentioning
confidence: 98%
“…While previous work in the literature has shown that the generation of predictions can serve word processing, phonemes in these experiments were either omitted (Bendixen et al, 2014), or replaced either by other phonemes (Cornell et al, 2013;Politzer-Ahles et al, 2016;Schluter et al, 2017) or by a non-linguistic sound (Kashino, 2006;Groppe et al, 2010). Because of this, changes in low level auditory features might have contributed to the recorded signals.…”
Section: Stimulimentioning
confidence: 99%
“…The significant effect of the T3 prime using the half-third sandhi variant supports the presence of a shared underlying representation for all the T3 tonal variants (Chien et al, 2016(Chien et al, , 2021, and cannot be explained by the surface representation view assuming the only storage of the surface form. However, the nature of the underlying representation is still debated, which has been argued to be the canonical form /214/ (as in the canonical representation view mentioned in Zhou and Marslen-Wilson, 1997), an abstract Low tone (e.g., Cheng, 1968), or an underspecified representation (e.g., Politzer-Ahles et al, 2016). Based on recent priming studies, it is probable that the underlying tone of T3 is represented as an abstract Low tone (Chien et al, 2020(Chien et al, , 2021Meng et al, 2021), but other studies have reported inconsistent findings (Politzer-Ahles et al, 2016;Zhou and Marslen-Wilson, 1997).…”
Section: Implications For Other Issuesmentioning
confidence: 99%
“…However, the nature of the underlying representation is still debated, which has been argued to be the canonical form /214/ (as in the canonical representation view mentioned in Zhou and Marslen-Wilson, 1997), an abstract Low tone (e.g., Cheng, 1968), or an underspecified representation (e.g., Politzer-Ahles et al, 2016). Based on recent priming studies, it is probable that the underlying tone of T3 is represented as an abstract Low tone (Chien et al, 2020(Chien et al, , 2021Meng et al, 2021), but other studies have reported inconsistent findings (Politzer-Ahles et al, 2016;Zhou and Marslen-Wilson, 1997). As the current study was not designed to test the nature of the underlying representation, further research is still required.…”
Section: Implications For Other Issuesmentioning
confidence: 99%
See 1 more Smart Citation